Effects of Sexual Function, Social Media Use, and Self‐Efficacy on Quality of Life Among Home Parenteral Nutrition Patients. Issue 5 (5th August 2020) - Kot, Dominika; Ławiński, Michał; Słodkowski, Maciej; Kagan, Ilya; Hellerman, Moran; Theilla, Miriam
Abstract: Background: Quality of life (QOL) of home parenteral nutrition (HPN) patients is a critical issue for functioning and survival. This study evaluates the roles of sexual function (SF), self‐efficacy (SE), and the use of social media (USM) in the QOL of HPN patients. Materials and methods: The study model investigates the independent variables USM and SF and the dependent variable QOL, and SE is a mediator variable between SF and USM. Results: We included 203 participants with HPN who completed self‐administered, validated questionnaires for QOL, SF, SE, and USM. Statistical analysis included a t ‐test, Sobel test, bootstrapping method, and Pearson correlations between variances. The mean HPN duration was 10.5 ± 8 years. Results show a significant correlation between QOL scores and SF ( P = .001). USM was positively correlated with SE ( P = .001). SE as a mediator between USM and SF was supported by significant results in the Sobel test. Patients with a stoma were significantly less sexually active and had lower SE ratings than those without a stoma. Conclusion: Physical changes that affect SE and boost social relationships by allowing emotional support through social networks are important factors for QOL improvement. These findings may guide health professionals in the management of HPN patients.